Psychosocial and information needs of people affected by colorectal cancer are poorly met during follow-up. Issue 3 (17th March 2011) - Kidd, Lisa
Abstract : Commentary on: Beaver K Latif S Williamson S . An exploratory study of the follow-up care needs of patients treated for colorectal cancer. J Clin Nurs 2010 ;19 :3291 –300 .